2015
DOI: 10.1016/j.chb.2015.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Individual and social benefits of online discussion forums

Abstract: a b s t r a c tThere has been much debate surrounding the potential benefits and costs of online interaction. The present research argues that engagement with online discussion forums can have underappreciated benefits for users' well-being and engagement in offline civic action, and that identification with other online forum users plays a key role in this regard. Users of a variety of online discussion forums participated in this study. We hypothesized and found that participants who felt their expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 74 publications
4
91
1
3
Order By: Relevance
“…Previous studies have also shown that participants in online support groups find it easier to discuss grief issues with their group than with family members or friends, as the group members show better understanding and are easier to reach for support and help (Feigelman et al, 2008;Oliveri, 2003;Pendry & Salvatore, 2015). Participation in different kinds of digital grief forums can bring bereaved people together in their grief work to form communities and also increase the possibility to maintain and enhance their relationships and bonds to the deceased (Bailey, Bell, & Kennedy, 2015;Moss, 2004;Roberts, 2004;Sofka, Cupit, & Gilbert, 2012), and a majority of the users seem to find the support groups beneficial and also show some improvement regarding well-being and depression (Kramer et al, 2015).…”
mentioning
confidence: 99%
“…Previous studies have also shown that participants in online support groups find it easier to discuss grief issues with their group than with family members or friends, as the group members show better understanding and are easier to reach for support and help (Feigelman et al, 2008;Oliveri, 2003;Pendry & Salvatore, 2015). Participation in different kinds of digital grief forums can bring bereaved people together in their grief work to form communities and also increase the possibility to maintain and enhance their relationships and bonds to the deceased (Bailey, Bell, & Kennedy, 2015;Moss, 2004;Roberts, 2004;Sofka, Cupit, & Gilbert, 2012), and a majority of the users seem to find the support groups beneficial and also show some improvement regarding well-being and depression (Kramer et al, 2015).…”
mentioning
confidence: 99%
“…First, being similar in status to others can activate a motivation to display (or affirm) one's own status (Ordabayeva and Chandon 2011;Charles and Lundy 2013;Kuziemko et al 2014). Second, in an online context, status information such as tenure, posting frequency, or review helpfulness indicates that an individual has successfully participated in the community, providing needed and useful information (Pendry and Salvatore 2015). Thus, when a consumer contributes WOM after an individual who is the same status as her, the consumer should be motivated to affirm or signal the status they have achieved.…”
Section: Behavioral and Linguistic Mimicrymentioning
confidence: 99%
“…Specifically, we should see greater cognitive and descriptive word mimicry when consumers share status with a previous poster, as these word categories allow consumers to demonstrate and assert their own status and achievements. Cognitive words (e.g., think, realize) help one to reason or explain, answer questions, provide arguments, and justify opinions (Pennebaker et al 2007), all of which should be instrumental to achievement in a WOM context (Pendry and Salvatore 2015). Indeed, explaining language in online reviews can increase perceived review helpfulness and product choice (Moore 2015).…”
Section: Wom Goals and Linguistic Mimicrymentioning
confidence: 99%
See 1 more Smart Citation
“…Using a certain model does not insure learning; Dysthe (2001) shows that the way the assignment is formulated is crucial for the dialogue and thereby for what the students can learn. An aspect found to be important for engagement in forums is well-being (Pendry and Salvatore 2015), which is not always easy to build into the course design.…”
Section: Literature Reviewmentioning
confidence: 99%